Pengembangan Komik Berbasis Karakter pada Pembelajaran Pecahan di Kelas V SD - Syafitri, Julia; Sukmawarti, Sukmawarti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The problem raised by the author in this study is that the use of interesting learning media on Fractions material is rarely used. And the use of learning media is still less varied for students, because the teacher only conveys material using learning media in the form of pictures in student textbooks. And rarely develop learning media in the form of character-based comics. Therefore, the author aims to determine the feasibility and produce character-based comic learning media in Mathematics learning with fractions for elementary school students. This research is a type of Research and Development (R&D) research with a 4D model developed by Thiagarajan (1974) which includes four steps: define, design, development and disseminate. But modified into a 3D model. The subjects in this study were material expert validators, media experts and teachers. The instrument used to collect data is a questionnaire. The questionnaire will be assessed by selecting